The rise of Islamic state : ISIS and the new Sunni revolution - Cockburn, Patrick, 1950- (London : Verso, 2015)
"Out of the failures of Iraq and Afghanistan, the Arab Spring and Syria, a new threat emerges. While Al Qaeda is weakened, new jihadi movements, especially ISIS, are starting to emerge. In military operations in June 2014 they were far more successful than Al Qaeda ever were, taking territory that reaches across borders and includes the city of Mosul. The reports of their military coordination and brutality are chilling. While they call for the formation of a new caliphate once again the West becomes a target. How could things have gone so badly wrong? In THE RISE OF ISLAMIC STATE, Cockburn analyzes the reasons for the unfolding of US and the West's greatest foreign policy debacle and the impact that it has on the war-torn and volatile Middle East"--
Preface : the hundred days -- The rise of ISIS -- The Battle of Mosul -- In denial -- Jihadis on the march -- The Sunni resurgence in Iraq -- Jihadis hijack the Syria uprising -- Saudi Arabia Tries to Pull Back -- If It Bleeds It Leads -- Shock and War.
"First published under the title The Jihadis return by OR Books, New York and London, 2014"--T.p. verso.
Includes index.
Keywords: IS (Organization); Terrorism -- Middle East; Terrorism -- Religious aspects -- Islam; HISTORY / Military / Iraq War (2003-).; Middle East -- History -- 21st century